Pengaruh Strategi Pembelajaran Discovery Berbantu Aplikasi Kelas Pintar terhadap Kemampuan Literasi Digital Siswa pada Materi Sistem Pernapasan Manusia - Hartati, Sri; Ulfa, Syarifah Widya (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to determine the effect of discovery learning strategies assisted by smart classroom applications on digital literacy skills in students and to compare the experimental class's digital literacy better than the control class after being given treatment. This type of research is a quasi-experimental research with a pretest-posttest control group research design. Data was collected using an instrument in the form of a questionnaire to measure students' digital literacy skills. The population and sample in this study were students of SMP IT Al-Hijrah 2 Laut Dendang class VIII B totaling 30 students and class VIII C totaling 30 students. In determining the pretest and posttest, the instrument validity test was carried out in the form of a questionnaire that had been validated by the validator. After obtaining data from the results of the pretest and post-test, The post-test results were obtained by class VIII C as the experimental class with an average value of 81 and Class VIII B as the control class with an average value of 65, namely that the calculation of the t-test on the posttesttcount (15.897) > ttable (2.001) and sig. (2-tailed) = 0.000 where (0.000 < 0.05) with a 95% confidence level the data is significant. Then Ha accepted these things showing that 1)There is an effect of using discovery learning strategies assisted by smart classroom applications on students' digital literacy skills,2) The experimental class that uses the discovery learning model on digital literacy skills in students is higher than the control class that uses the conventional learning model, namely the lecture method.